Watching-eye effect e nudge conformistico: meta-analisi di un’ottemperanza inconsapevole (con molti limiti) - Cominelli, Luigi (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
In complex and democratic societies, the activity of control and enforcement cannot be delegated to an intrusive and omnipresent police apparatus. Even more than in pre-industrial societies, obeyance to the rules of coexistence must be based on spontaneous compliance. The function of social control, which is already favored by the tendential prosociality of human conduct, is also generally based on the threat of a negative consequence. Today we tend to view these threats of punishment as necessarily explicit and direct, and codes of legal, moral and religious norms serve this purpose. However, it cannot be excluded that the same goal can be achieved in many situations, sometimes even more effectively, by leveraging an unconscious or semi-unconscious bias through a nudge, which surreptitiously directs us towards the behavior deemed socially desirable through a subtle social benchmark. This effect, which we could also define as conformist bias, seems to be achieved through visual stimuli such as the watching-eye, i.e. the more or less stylized image of an eye or of a person observing, placed in salient places from the point of view of the individual decision on the action to be taken. It has been hypothesized that our neural circuits are structured to automatically perceive the “social gaze”, and provide the reactions necessary to re-orient our behavior. The photographic or stylized image of this watching-eye would seem to obtain an effect of greater compliance in situations in which it is not possible to obtain widespread personal surveillance, to an even greater extent than video surveillance equipment. Numerous empirical researches have subjected this hypothesis to empirical verification, and this contribution proposes to offer a review of it with respect to the issues involving social norms of a legal nature, as well as investigating the moral and theoretical implications that derive from it.